Tailing cementing material composite exciting agent ratio decision-making method

By calculating the weighted strength and cost of filler, defining the cost-effectiveness of gelling materials, and using regression analysis to optimize the proportion of exciter, the problem of long research and development cycle of gelling materials in the existing technology and difficulty in adapting to different mining methods is solved, and the development of low-cost and high-performance new filling gelling materials is achieved.

CN119694464AActive Publication Date: 2025-03-25QIANAN WEISHENG SOLID WASTE ENVIRONMENTAL PROTECTION IND CO LTD

Patent Information

Application Number
CN202510087223.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-03-25
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

During the research and development of existing new filling gelling materials, the test workload is large and the R&D cycle is long, making it difficult to quickly adapt to different mining methods and variable solid waste characteristics, and the impact of the cost-effectiveness of gelling materials in the ratio decision is not considered.

Method used

By calculating the weighted strength of the cemented filler and the cost of the gelled material, the cost-effectiveness of the gelled material is defined, and the relationship function of the cost-effectiveness and the ratio of the alkali and salt exciter is fitted using the regression analysis method to solve its extreme value to optimize the ratio of the composite exciter.

Benefits of technology

It has achieved rapid decision-making on the composite exciter ratio of new filling gelling materials, developed gelling materials with the lowest cost and stronger mechanical properties, suitable for complex and changeable solid waste resources, and promoted the scale and high-value application of industrial solid waste in filling mining.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119694464A_ABST
    Figure CN119694464A_ABST
Patent Text Reader

Abstract

The invention discloses a matching decision-making method for a tailing cementing material composite exciting agent, and belongs to the technical field of energy conservation, environmental protection and green mining filling. The method comprises the following implementation steps: determining the concentration range of filling slurry according to the grain size grading of mineral processing tailings, and determining the slurry concentration of a cemented filling body strength test; designing the ratio range of the alkali solid waste excitant and the salt solid waste excitant, and carrying out a tailing cemented filling body strength test; calculating the weighted strength of the filling body and the cost performance of the cementing material; polynomial regression analysis is adopted, a relation function between the cost performance of the cementing material and the ratio of alkali to salt is fitted, the optimal ratio of alkali to salt of the composite activator is obtained, and the activator ratio of the green filling cementing material for tailings is decided. When the method is adopted for optimization design of the tailing filling cementing material, the test workload is small, the solving difficulty of the optimal proportion of the excitant is low, and the green filling cementing material with high cost performance and high adaptability can be prepared, so that popularization and application of a tailing filling mining technology in mine filling are promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of green filling mining for resource utilization of various solid wastes, and in particular to a method for deciding the proportion of a composite activator for green and environmentally friendly tailings filling cementitious materials. Background Art

[0002] In order to achieve safe, environmentally friendly and green mining of mineral resources and clean production of mining enterprises, tailings filling mining is the first choice. However, the mining process of tailings filling mining is complex, the production capacity is low, the mining cost is high, and the cost of filling cementitious materials accounts for the main part of the total filling mining cost. Therefore, the development and industrial application of low-cost new filling cementitious materials is the only way to improve the economic and environmental benefits of tailings filling mining.

[0003] Over the past decade, the use of various metallurgical industrial solid wastes such as slag, steel slag, and desulfurized gypsum to develop new green and environmentally friendly filling cementitious material proportions and preparation methods has been a focus of research on tailings filling mining technology. At present, many invention patents and academic papers on new filling cementitious materials have been published.

[0004] CN104529197A (a method for preparing a novel composite cementitious material) discloses the ratio and method of preparing a composite activator using desulfurized gypsum, sodium silicate and calcium oxide. CN109320176A (a novel coal slime cementitious material for mining filling) discloses the formula and preparation method of preparing a filling material using fine coal powder, coal slime, cement and special additives. CN109336433A (a method for producing a novel cementitious material using industrial waste slag and furnace slag) proposes the ratio and preparation method of producing a novel cementitious material using industrial waste slag and furnace slag as raw materials. CN110330243A (a novel cementitious material for clinker-free tailings filling) proposes the formula of preparing a novel cementitious material using slag powder, fly ash, steel slag powder, desulfurized gypsum, sodium sulfate, red mud and triethanolamine. CN111187010A (A new type of composite cementitious material with high performance and low cost without clinker) invented a new type of composite cementitious material formula composed of quicklime, desulfurized ash, modified materials and composite admixtures. CN111217543B (A multi-component synergistic tailings filling cementitious material and its preparation method) uses fine tailings, phosphogypsum, stearic acid, liquid sodium silicate, high molecular polymer, sulfate activator, alkaline solid activator, water reducer, slag, steel slag and desulfurized gypsum to prepare tailings filling cementitious material and its formula. CN116282984A (Green cementitious material, new roadbed material and its preparation method) discloses the formula of green cementitious material composed of desulfurized ash, steel slag powder, slag powder and construction waste micropowder. CN116496009A (Ultrafine tailings filling cementitious material mainly based on copper slag and fly ash and its filling material) proposes a formula for preparing ultrafine tailings filling cementitious material using copper slag powder, fly ash, cement clinker, high-strength gypsum powder and alkaline activator.

[0005] In summary, the invention technology of the new filling cementitious material disclosed earlier mainly provides a formula and preparation method of a filling cementitious material. Since the utilization of solid waste is subject to regional restrictions and different filling mining methods have different requirements for cementitious materials, the patent technology of the new filling cementitious material disclosed above is limited to specific mines, specific environments, specific regions and specific filling mining methods. Due to the complex and changeable components of industrial solid waste, it is difficult to obtain the expected results by only disclosing the formula of the new filling cementitious material; at the same time, the disclosed new filling cementitious material has not made any analysis and evaluation on the economic and environmental benefits of its solid waste utilization.

[0006] In view of the limitations of the earlier disclosed inventions, the recent research and development of new filling cementitious materials and the disclosed patent technologies involve new cementitious material ratio optimization methods. Chinese patents CN110655376B (a steel slag collaborative preparation of green cementitious materials and multi-objective optimization method), CN107311582B (a low-cost early strength cementitious material ratio decision method), CN107117888B (a mixed aggregate filling slurry ratio decision method for mining), CN113387671B (a green filling material ratio optimization method for water resistance stability of Dashui mine), CN103723967B (a filling cementitious material ratio decision method for mining), CN111191387B (a phosphogypsum-based cementitious material optimization method for improving the filling connection rate), CN111508566B (a preparation method for low-cost filling cementitious materials prepared by composite excitation of multiple solid wastes), etc., all disclose the optimization method of developing new cementitious materials using industrial solid waste. That is, taking the cost of cementitious materials as the optimization target and the safe production of cementitious materials in filling mines as the constraint condition, a new filling cementitious material ratio optimization model is established and solved, thereby obtaining the optimized formula of the new filling cementitious material. Compared with the early patent technology of new cementitious materials, the key technology of the recent patent is to make formula decisions by establishing and solving the optimization model of new filling cementitious materials, rather than just disclosing a new cementitious material formula. Therefore, the recent patent technology can adapt to the complex and changeable solid waste characteristics and the requirements of different mining methods for cementitious material characteristics. Obviously, the recently disclosed patent technology has significant advantages. Although recent invention patent technologies have made breakthroughs in the research and development of filling cementitious materials, the following major problems still exist: the experimental workload of new cementitious materials is large, the research and development cycle is long, the optimization model is difficult to solve, and it cannot quickly adapt to the requirements of different mining methods and variable solid waste characteristics to develop cementitious materials. For example, the post-stage filling mining method has high requirements for late strength and low requirements for early strength; while the downward layered filling mining method has high requirements for both early and late strength. The optimization model established with the filling mining cost as the optimization target cannot take into account the impact of the cost performance of new cementitious materials on its cementitious material ratio decision.

[0007] By analyzing the patent technologies of new cementitious materials disclosed in the early and recent period, the applicant believes that the core technology of all green and environmentally friendly filling cementitious materials developed from industrial solid waste is: generally using alkali activators, salt activators or alkali-salt composite activators to stimulate potentially active volcanic ash materials (such as blast furnace slag, fly ash) to make them undergo water hardening reaction, thereby preparing new filling cementitious materials. A large number of research practices on new filling cementitious materials have shown that the use of composite excitation to develop green filling cementitious materials can achieve the best results. From the above analysis, it can be seen that the key technology for developing green filling cementitious materials using industrial solid waste is to explore a fast, simple and reliable decision-making method for the ratio of alkali and salt of composite activators, which can not only develop new filling cementitious materials using various complex and changeable solid wastes, but also simply and quickly obtain the optimized formula for preparing new cementitious materials using two types of solid wastes, alkali and salt. Summary of the invention

[0008] In view of the shortcomings of the invention patents in the background technology, the patent technology disclosed in the present invention is characterized by: taking into account the requirements of different mining methods for the strength of the filling body and the potential variability of the physical and chemical components of industrial solid waste, different weights are taken for the strength of the filling body at different ages, and the weighted strength of the cemented filling body is calculated. Then, according to the utilization cost of industrial solid waste (the utilization cost of solid waste raw materials and the processing cost), the cost of green filling cementitious materials is calculated. The cost performance of cementitious materials is defined as the ratio of the weighted strength of the cementitious filling body to the cost of cementitious materials. According to the strength test of the cementitious filling body, the regression analysis method is used to fit the relationship function between the cost performance of the new cementitious material and the ratio of alkali and salt activators. By solving the extreme value of its relationship function, the ratio of the composite activator of the new filling cementitious material is optimized, thereby solving the defect that the cost performance of the new green cementitious material is not considered in the background technology. Optimizing the ratio of composite activators based on the cost-effectiveness of filling cementitious materials can be utilized to develop new filling cementitious materials with the lowest cementitious material cost and stronger mechanical properties, thereby promoting the large-scale and high-value application of various industrial solid wastes in filling mining.

[0009] The present application provides a tailings cementitious material composite activator ratio method, and the implementation steps are as follows: 1). Carry out particle size distribution analysis on the beneficiation tailings to obtain the content of -200 mesh fine sand and -400 mesh ultra-fine tailings in the tailings; determine the slurry concentration range for the fluidity and stability test of the tailings filling slurry; 2). According to step 1), the slurry lime-sand ratio is fixed, and the fluidity and stability tests are carried out within the slurry concentration range to obtain the test results of the consistency and water seepage rate of the tailings filling slurry; 3). According to step 2), the concentration of the filling slurry for the tailings cemented filling strength test is determined on the condition that the fluidity and stability of the filling slurry meet the requirements of gravity transportation of the slurry pipeline; 4). According to step 3), solid wastes such as converter slag, refined slag, magnesium slag or carbide slag are used instead of cement clinker as alkali activator, desulfurization gypsum from power plants and steel plants, phosphogypsum or fluorite from chemical enterprises are used as salt activator, and alkali-salt solid waste is used to prepare composite activator to activate potentially active volcanic ash materials such as blast furnace slag and / or fly ash, thereby preparing green filling cementitious materials. Based on research and development experience, determine the alkali and salt ratio range of the composite activator of green filling cementitious materials; 5). According to steps 3) and 4), a strength test of the green filling cementitious material tailings cemented filling body is conducted to obtain the test results of the 3-day and 7-day strength of the tailings cemented filling body respectively; 6). According to step 5), weight the 3-day and 7-day strength data of the tailings cemented filling body respectively to calculate the weighted strength of the cemented filling body; according to the utilization cost of solid waste raw materials and the processing and production cost of green cementitious materials, calculate the ratio of the strength of the tailings cemented filling body to the cost of cementitious materials, thereby obtaining the cost performance of green cementitious materials; 7). According to steps 5) and 6), calculate the average cost performance of the green cementitious material of the cementitious material composite activator alkali and salt; 8). According to step 7), the relationship function between the cost performance of green cementitious materials and the ratio of salt to alkali corresponding to the alkali and salt with the largest average cost performance of green cementitious materials is fitted by polynomial regression analysis; 9). According to step 8), the relationship function between the cost performance of green cementitious materials and the ratio of salt and alkali is derived, and the extreme value of the function is obtained by setting it to zero, and the alkali-salt ratio of the composite activator for filling the cementitious material is obtained: 10). Calculate the cost performance of green cementitious materials based on the two groups of activator ratios, compare the cost performance of the two groups of cementitious materials, and finally select the green cementitious material ratio with the activator ratio with the highest cost performance.

[0010] Preferably, in step 1), the tailings particle size distribution analysis specifically includes: analyzing the content of -200 mesh fine sand α% and -400 mesh ultrafine tailings β% in the tailings; determining the slurry concentration range for the tailings filling slurry working characteristic test m 1 %~ m 4 %; when α<70% and β<40%, the slurry concentration range is 66%~72%; when α<75% and β<50%, the slurry concentration range is 64%~70%.

[0011] Preferably, in step 2), the lime-sand ratio of the tailings filling slurry is selected to be 1:4.

[0012] Preferably, in step 3), the fluidity and stability requirements of the tailings filling slurry for pipeline gravity transportation are determined, and the consistency of the tailings filling slurry is determined. L i ≥13cm , water seepage rate W i ≤15% .

[0013] Preferably, in step 6), the weighted strength calculation formula of the cemented filling body is: R i q = q 3d × R ij 3d + q 7d × R ij 7d in, R i q is the weighted strength of the cemented filling body, q 3d is the weight of the 3-day strength of the cemented filling body, q 7d is the weight of the 7-day strength of the cemented filling body, R ij 3d The strength of the cemented filling body after 3 days. R ij 7d The 7-day strength of the cemented filling body. i It represents the test plan of cemented filling body. j Indicates the 3-day and 7-day strength of the cemented filling.

[0014] Preferably, in step 6), in the subsequent filling mining method, q 3d =0.3, q 7d =0.7; In the up-fill mining method, q 3d =0.4, q 7d =0.6; In the down-fill mining method, q 3d =0.5, q 7d =0.5.

[0015] Preferably, in step 9), The relationship function between the cost performance of green filling cementitious materials and the ratio of salt and alkali is derived and set to 0, thereby obtaining the extreme value of the relationship function. The solution formula is as follows: d C H T / db=d f 1 ( b 1 , b 2 , b 3 , b 4 ) / db=0 (1) d C K T / da=d f 2 ( a 1 , a 2 , a 3 , a 4 ) / da=0 (2) Solve equation (1) to obtain the ratio of salt activator in the composite activator of green cementitious materials: b ; Solve equation (2) to obtain the ratio of alkali activator in the composite activator of green cementitious materials: a .

[0016] Compared with the patent technology disclosed in the background technology of filling cementitious materials, the patent of the present invention not only has a small experimental workload, a short research and development cycle and a small difficulty in solving the stimulator formula, but also can quickly make decisions on the ratio of composite stimulators based on limited experimental work, and make decisions on the ratio of composite stimulators based on the cost-effectiveness of filling cementitious materials. It can also use a variety of complex and changeable solid wastes to develop new green filling cementitious materials, and can also obtain low-cost and high-performance new filling cementitious materials, providing green filling cementitious materials for different filling mining methods, thereby promoting green mine construction. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The curve showing the relationship between the strength of the cementitious material filling body and the salt ratio when the alkali activator is 12% in the embodiment of the present invention; Figure 2 The curve showing the relationship between the performance-price ratio of the gelling material and the salt ratio when the alkali activator is 12% in the embodiment of the present invention; Figure 3 The relationship curve between the strength of the cementitious material filling body and the alkali ratio when the salt activator is 10% in the embodiment of the present invention; Figure 4 This is the relationship curve between the cost performance of the cementitious material and the alkali ratio when the salt activator is 10% in the implementation case of the present invention. DETAILED DESCRIPTION

[0018] In order to more clearly illustrate the decision-making method for the ratio of the composite activator of the green and environmentally friendly tailings cementitious material disclosed in the present invention, as well as the key technologies and implementation steps involved, a detailed description will be given below in conjunction with the accompanying drawings and specific implementation cases.

[0019] In a specific implementation scheme, the following 6 steps are included: Step 1: Tailings particle size analysis and slurry concentration range determination (1) The whole tailings of a lead-zinc mine in Inner Mongolia were sampled and analyzed for particle size distribution. The particle size distribution results of the whole tailings are shown in Table 1. According to Table 1, the content of -200 mesh (-75 μm) fine tailings in the whole tailings is α=56.48%, and the content of -400 mesh (-38 μm) ultrafine tailings is β=26.87%.

[0020] (2) Based on the content of fine tailings and ultrafine tailings in the whole tailings and with the help of research and development experience, the slurry concentration range for the tailings filling slurry fluidity and stability test was determined to be 62%~68%.

[0021] Table 1 Test results of particle size distribution of whole tailings Step 2: Determine the strength test concentration based on the slurry working characteristics test (1) Based on the tailings slurry concentration range of 62% to 68% determined in step 1, the lime-sand ratio was 1:4 (the lime-sand ratio does not affect the optimization of the cementitious material ratio), and the full tailings filling slurry fluidity (consistency) and stability (water seepage rate) test was carried out. The test results are shown in Table 2. (2) According to the tailings filling slurry to meet the fluidity and stability requirements of pipeline gravity transportation ( L≥13cm , W≤ 15% ), and the slurry working characteristics test results in Table 2, it is determined that the tailings slurry concentration for the tailings cemented backfill strength test is 66%.

[0022] Table 2 Test results of working characteristics of tailings filling slurry Step 3: Strength test of tailings filling body with cementitious material (1) Tailings slurry concentration determined in step 2 m =66% and lime-sand ratio 1:4. Use converter slag as alkali activator and desulfurized gypsum as salt activator. Develop green cementitious material composite activator test. With the experience of cementitious material research and development, design the alkali activator ratio a i Ratio of salt activator b jRange is a i =10%~16%、b j =4%~10% ( i, j =1, 2, 3, 4) 。

[0023] (2) According to the ratio of tailings slurry to sand and the ratio of alkali to salt in cementitious materials, a 2% incremental ratio was used to conduct a tailings cementitious filling strength test in accordance with the cement mortar strength test method B / T17671-1999 to obtain the tailings cementitious filling strength R ij 3d , R ij 7d (See Tables 3 and 4).

[0024] Table 3 Test results of tailings filling strength based on the ratio of composite activator for new filling cementitious materials Table 4 Test results of tailings filling strength based on the ratio of composite activator for new filling cementitious materials Step 4: Fitting the relationship function between the performance-price ratio of cementitious materials and the ratio of salt and activator (1) According to Table 3 and Table 4, the 3d and 7d strength of the filling R ij 3d , R ij 7d ( i= 1~4 、j= 1~4), according to the filling body strength requirements of the subsequent filling mining method, the 3d and 7d strength of the filling body are weighted respectively R q 3d , R q 7d , calculate the weighted strength of the filling R ij q = R ij 3d R q 3d + R ij 7d R q 7d(See Tables 3 and 4).

[0025] (2) Calculate the cost of cementitious materials based on the solid waste materials and processing costs of alkali and salt activators used in green cementitious materials C ij T ; According to the weighted strength of the filling R ij q , calculate the performance-price ratio of cementitious materials: C ij X = R ij q / C ij T ( i =1, 2, 3, 4 、j= 1, 2, 3, 4) (see Tables 3 and 4); (3) According to the performance-price ratio of cementitious materials in Tables 3 and 4, the average performance-price ratio of cementitious materials was calculated for each alkali and salt activator ratio, and the average performance-price ratio of alkali activator was obtained. C i X ( i =1, 2, 3, 4) (see Table 3) and the mean of salt stimulants C j X ( j =1, 2, 3, 4) (see Table 4); (4) According to Table 3 and Table 4, the average cost performance of alkali and salt activated cementitious materials C i T ( i =1, 2, 3, 4), C j X , ( j =1, 2, 3, 4), respectively determine the alkali activator ratio with the maximum average cost performance of the cementitious material: C H T =Max C i T = C 2 T =25.7kPa / yuan (see Table 5), and the salt activator ratio with the highest cost performance average: C K T =Max C j T = C4 T =24.5kPa / yuan (see Table 6).

[0026] Table 5 The ratio of alkali activator to salt activator corresponding to the maximum average cost performance of new cementitious materials Table 6 The ratio of salt activator to alkali activator corresponding to the maximum average cost performance of new cementitious materials (5) According to the alkali ratio with the highest average cost performance of cementitious materials in Table 5 a 2 =12% ​​and the corresponding salt activator ratio b j ( j = 1, 2, 3, 4), the relationship curve between the 3d and 7d strength of the cementitious material filling and the salt activator ratio is shown in Figure 1 The relationship curve between the performance-price ratio of cementitious materials and the ratio of salt activators is shown in Figure 2 .according to Figure 2 The fitting function of the maximum mean performance-price ratio of cementitious materials and the salt activator ratio with a medium alkali ratio of 12% is as follows: C HX=-0.0491 b 2 + 1.1872 b + 20.053 R² = 0.8761 (1) (6) According to the salt ratio with the highest average cost performance of cementitious materials in Table 6 a 2 =10% and the corresponding alkali ratio a i ( i = 1, 2, 3, 4), the relationship curve between the 3d and 7d strength of the cementitious material filling and the salt activator ratio is shown in Figure 3 The relationship curve between the performance-price ratio of cementitious materials and the ratio of salt activator is shown in Figure 4 .according to Figure 4 The alkali activator is 12%, and the fitting function of the maximum mean cost performance of the cementitious material and the salt activator ratio is: C K X = -0.3125 a 2 +7.545 a - 19.36 R² = 0.8488 (2) Step 5: Determine the alkali-salt ratio of the composite activated gelling material with the highest cost performance Derivative the relationship functions of equation (1) and equation (2) respectively and set them to 0: d C HX / d b =d(-0.0491 b 2 + 1.1872 b + 20.053) / db=0 (3) Calculate the ratio of composite activator to alkali salt activator: a =12%, b =12.09%; d C K X / d a =d(-0.3125 a 2 +7.545 a - 19.36) / d a =0 (4) Obtain the ratio of alkali and salt activators in the composite activator: a =12.07%, b =10%.

[0027] Step 6. Final decision on the ratio of alkali salt of composite activator of cementitious material Through the method for mixing alkali and salt ratios of composite activators for filling gelling materials disclosed in the present application, two groups of alkali-salt activator ratios are obtained: (1) a =12% ​​and b =12.09%; (2) a =12.07% and b =10%. Substituting the two groups of activators into formula (1) and formula (2) respectively, the cost performance of green cementitious materials is calculated as: C H X =-0.0491×12.092 + 1.1872×12.09+20.053=27.2kPa / yuan (5) C K X =-0.3125×12.07 2 + 7.545×12.07 - 19.36=26.2 kPa / yuan (6) Comparing the performance-price ratio of the two groups of activator ratios, it can be seen that the activator ratio of group (1) is greater than that of group (2). The final ratio of the composite activator ratio of the cementitious material is determined as: a =12% ​​and b =12.09%.

[0028] According to the optimization decision-making method of this patent, the optimized ratio of a new filling cementitious material in a lead-zinc mine in Inner Mongolia was obtained. The steel slag, slag and desulfurized gypsum of the local metallurgical industry solid waste were used to prepare the new filling cementitious material. The strength of the tailings cemented filling body of the cementitious material was significantly improved compared with the traditional optimized ratio (17% alkali activator and 3% salt activator), and the cost of the cementitious material was reduced to (111.6 / 124.8) = 89.4%. The new cementitious material obtained by this application has been applied in a large iron mine in Hebei Province. The large iron mine requires about 900,000 tons of new tailings filling cementitious material every year. According to this calculation, the application of the new cementitious material in the mine when it reaches full production can obtain an economic benefit of 30 yuan / t×900,000 tons / year=27 million yuan / year.

[0029] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may be modified and varied in various ways. For example, the refined slag (white slag) of steel enterprises and reduced magnesium slag may be used instead of converter slag, and phosphogypsum and fluorgypsum may be used instead of desulfurized gypsum. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for determining the proportion of composite activators for tailings cementitious materials, characterized in that: Here are the steps: 1). Carry out particle size distribution analysis on the beneficiation tailings to obtain the content of -200 mesh fine sand and -400 mesh ultra-fine tailings in the tailings; thereby determine the filling slurry concentration range for the slurry fluidity and stability test; 2). According to step 1), the lime-sand ratio is fixed, and the fluidity and stability tests are carried out within the slurry concentration range to obtain the test results of the consistency and water seepage rate of the tailings filling slurry; 3). According to step 2), the concentration of the filling slurry for the strength test of the tailings cemented filling body is determined based on the fluidity and stability of the tailings slurry to meet the requirements of pipeline gravity transportation; 4). According to step 3), select alkaline solid wastes such as converter slag, refined slag or magnesium slag as alkali activators, and sulfide solid wastes such as desulfurized gypsum, phosphogypsum or fluorinated gypsum as salt activators, and design the alkali and salt ratio range of the composite activator of tailings green cementitious materials with the help of experience; 5). According to steps 3) and 4), an alkali salt composite activator is used to compositely activate the potential activity of volcanic ash materials such as blast furnace slag and / or fly ash, and a tailings cemented filling strength test is carried out to obtain the 3-day and 7-day strength test data of the tailings cemented filling; 6). According to step 5), the weighted values ​​of the 3-day and 7-day strengths of the tailings cemented filling body are taken respectively to calculate the weighted strength of the tailings cemented filling body; according to the utilization cost of solid waste raw materials and the processing cost of green cementitious materials, the ratio of the filling body strength to the cementitious material cost is calculated to obtain the cost performance of the green cementitious material; 7). According to steps 5) and 6), calculate the average cost performance of green cementitious materials with the ratio of green cementitious materials composite activator alkali and salt respectively; 8). According to step 7), the relationship function between the cost performance of green cementitious materials and the ratio of salt to alkali corresponding to the alkali and salt activators with the largest average cost performance of green cementitious materials is fitted by polynomial regression analysis; 9). According to step 8), the relationship function between the cost performance of green gelling materials and the ratio of salt and alkali is derived, and the extreme value is set to zero, thereby obtaining the alkali-salt ratio of the composite activator of the green gelling material: 10). The cost performance of green cementitious materials is calculated based on the ratio of the two groups of composite activators. By comparing the cost performance of the two groups of green cementitious materials, the activator of the green cementitious material with the highest cost performance is taken as the optimal ratio.

2. The method for determining the ratio of composite activator of tailings green cementitious material according to claim 1 is characterized in that: In the step 1), the tailings particle size distribution analysis specifically includes: According to the content of -200 mesh fine sand α% and -400 mesh ultra-fine tailings β% in the tailings, the concentration range of the tailings filling slurry working characteristics test is determined. m 1%~ m 4%; when α<70% and β<40%, the slurry concentration range is 66%~72%; when α<75% and β<50%, the slurry concentration range is 64%~70%.

3. The method for determining the ratio of composite activator of tailings green cementitious material according to claim 1, characterized in that: In the step 2), the lime-sand ratio of the tailings filling slurry is selected to be 1:

4.

4. The method for determining the ratio of composite activator for tailings cementitious materials according to claim 1, characterized in that: In step 3), according to the fluidity and stability requirements of the tailings filling slurry pipeline gravity transportation: determine the consistency of the tailings filling slurry L i ≥13cm , water seepage rate W i ≤15% .

5. The method for determining the ratio of composite activator for tailings cementitious materials according to claim 1, characterized in that: In step 6), the weighted strength calculation formula of the tailings cemented filling body is: R i q = q 3d × R ij 3d + q 7d × R ij 7d in, R i q Representative i Weighted strength of cemented filling body for each test scheme, q 3d Represents the weight of the 3-day strength of the tailings cemented filling body, q 7d Represents the weight of the 7-day strength of the tailings cemented filling body, R ij 3d represents the 3-day strength value of the tailings cemented filling body. R ij 7d Represents the 7-day strength value of tailings cemented filling body.

6. The method for determining the ratio of composite activator for tailings cementitious materials according to claim 5, characterized in that: In step 6), for the subsequent filling mining method, q 3d =0.3, q 7d =0.7; For upfill mining method, q 3d =0.4, q 7d =0.6; For down-fill mining method, q 3d =0.5, q 7d =0.

5.

7. The method for determining the ratio of composite activator for tailings cementitious materials according to claim 1, characterized in that: In the step 9), the relationship function between the cost performance of green cementitious materials and the ratio of salt and alkali is derived and set to 0, thereby solving the extreme value of the relationship function, and the calculation formula is as follows: d C H T / db=d f 1( b 1、 b 2、 b 3、 b 4) / db=0 (1) d C K T / da=d f 2( a 1、 a 2、 a 3、 a 4) / from=0 (2) Solve equation (1) to obtain the salt activator ratio in the green cementitious material composite activator b ; Solve equation (2) to obtain the alkali activator ratio in the green cementitious material composite activator: a .

Citation Information

Patent Citations

  • A method for determining the proportion of backfill cementitious materials used in mining

    CN103723967B

  • Preparation method of novel composite cementing material

    CN104529197A

  • A method for determining the proportion of mixed aggregate backfill slurry for mining

    CN107117888B

  • A low-cost method for determining the proportions of early-strength cementitious materials

    CN107311582B

  • Novel mineral coal slime cementing material for filling mining

    CN109320176A

Cited By

  • A method for precise blending of cementitious raw materials in multiple mining scenarios based on a mixing algorithm model

    CN122667896A